Analysis of volatility volume and open interest for Nifty Index futures using GARCH analysis and VAR model - Parizad Phiroze Dungore; Sarosh Hosi Patel (International Journal of Financial Studies, 2021)
The generalized autoregressive conditional heteroscedastic model (GARCH) is used to estimate volatility for Nifty Index futures on day trades. The purpose is to find out if a contemporaneous or causal relation exists between volatility volume and open interest for Nifty Index futures traded on the National Stock Exchange of India, and the extent and direction of these relationships. A complete absence of bidirectional causality in any particular instance depicts noise trading and empirical analysis according to this study establishes that volume has a stronger impact on volatility compared to open interest. Furthermore, the impulse originating from volatility of volume and open interest is low.
Keywords: G2; G4; C30; C50; C58; 330; causal relation; GARCH model; National Stock Exchange of India; Nifty Index futures; open interest; volatility; volume